2022
DOI: 10.1097/hco.0000000000000960
|View full text |Cite
|
Sign up to set email alerts
|

Diet and vascular risk

Abstract: Purpose of reviewThe basis for the prevention and treatment of cardiovascular disease (CVD) inevitably involves lifestyle modification, including dietary pattern (DP). The aim of this review is to address the different models of healthy DP with their peculiarities and nutritional components as well as their importance in the management of CVD. Recent findingsClassical cardiovascular risk factors such as hypertension, dyslipidaemia and diabetes are strongly influenced by diet and physical activity. However, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…While regulatory bodies generally consider ASwt safe at recommended intake levels, some observational studies suggest an association between high ASwt consumption and an increased risk of CVD. [5][6][7][8] This study did reveal potential interactions between ASwt, particularly As and Su, with cellular targets (CAPN1, LTA4H, MKNK2, ITGA2, and HDAC1) involved in various physiological processes. Notably, some of these targets are linked to functions relevant to CVD development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While regulatory bodies generally consider ASwt safe at recommended intake levels, some observational studies suggest an association between high ASwt consumption and an increased risk of CVD. [5][6][7][8] This study did reveal potential interactions between ASwt, particularly As and Su, with cellular targets (CAPN1, LTA4H, MKNK2, ITGA2, and HDAC1) involved in various physiological processes. Notably, some of these targets are linked to functions relevant to CVD development.…”
Section: Discussionmentioning
confidence: 99%
“…Despite safety evaluations, several studies suggest potential health risks associated with chronic consumption of ASwt. A WHO systematic review 3 revealed that replacement of ASwt with sugar does not provide a means for weight management in the long-term, and several studies have discovered a positive correlation between long term ASwt consumption and risk of developing cardiovascular disease [5][6][7][8] , type 2 diabetes mellitus 6,[8][9][10][11] , and mortality in adults 6,8,9,12 . Current literature also reveals other concerning associations between ASwt consumption and various routinely observed clinical conditions, including heightened risks of developing cancer [13][14][15] , chronic kidney disease 16,17 , adiposity related diseases 8,9,18,19 , as well as non-alcoholic fatty liver disease 20 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely demonstrated that lifestyle improvement is the cornerstone of CVD prevention [ 21 ]. Among lifestyle strategies, a healthy diet is one of the most effective strategies for attaining BP reduction and control [ 22 ]. In effect, a large body of evidence suggests that some food or food components—along with low-dose daily intake of sodium—might provide a specific advantage for BP [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to epidemiological data (often related to the Mediterranean diet [ 118 ]) linking a plant-based diet with lower blood pressure [ 119 ], some human studies provided direct evidence of the (poly)phenol-induced increase in vasomotion. Three examples are worth mentioning.…”
Section: Methodsmentioning
confidence: 99%